PERTANGGUNGJAWABAN DIREKSI KARENA KELALAIAN ATAU KESALAHANNYA YANG MENGAKIBATKAN PERSEROAN PAILIT - MARTHA VIVY; RAMLI SIREGAR; WINDHA WINDHA (TRANSPARENCY, 2013)
Company Limited as a legal entity has the responsibility to limit. He admitted the company as an institution incorporated under the Act, has placed the company as a legal subject that is considered competent to perform legal actions and be responsible for all legal actions he made. One of the important organs in the course of the company are directors. Directors are given confidence by the shareholders through the mechanism of the General Meeting of Shareholders to be organ of the company who takes care of and manage the company. In this case, if there is loss of wealth caused by the actions of the company's directors are incorrect, negligent or committed an unlawful act, the company is the only party entitled to claim the loss. There is no clear and definite statement regarding the position of directors in a company, which is obviously the company's board of directors is the governing body of the most high, and has the right and authority to run the company. In other words, the board has the scope of duties as a board member of the company. The Company can’t be separated from the possible inability to pay debts that have matured and can be charged by creditors, then the existence of such circumstances, the company may be filed for bankruptcy. In the care of the company, directors should not be mistaken or negligent. Directors said wrong or negligent which resulted in the company declared bankruptcy, namely the lack of good faith by the board of directors to pay off debts to creditors. Directors negligent carry out debt payments to creditors. So the directors can be held liable jointly and severally through bankruptcy proceedings in the Commercial Court.   Kata Kunci: Pailit, Perseroan, Tanggung Jawab Direksi